Uma análise da informação turística disponível na internet sobre Arraias-TO - Souza, Sandra Garcia de (Universidade Federal do Tocantins, 2021)
Many tourists, especially those traveling on their own, rely on the information they find on the internet to decide and organize their travels. Without leaving your residence the tourist finds information about the tourist attractions, historical-cultural and natural, food equipment, lodging and hires the services that you need for your trip. Using the Google search tools, the Youtube video tool and the social network Facebook this work has identified if a potential tourist, who wants to come to the Municipality of Arraias-TO, finds on the Internet information about the tourist attractions, historical-cultural, natural , food and lodging equipment. The searches yielded a total of 261 sites, of which 202 were for Google searches, 29 for YouTube videos and 30 for Facebook pages. It was possible to perceive that the information divulged relates to historical-cultural issues (religious festivals, carnival, origin of the city, typical cuisine) natural attractions and little information about commercial enterprises and how to contract their services. A tourist who searches for information and wants to organize his trip to Arraias will find it difficult to do so via the internet. Considering these results, this work points out the need to create a site that brings together in a single page, information that allows the tourist to decide and organize a trip to Arraias-TO.